Chemical concentration calculation based on spectrogram - Siti Nur Aishah, Ahmad Shah (2012)
In this project, the chemical concentration identified based on spectrogram. In chemistry, concentration is defined as the abundance of a constituent divided by the total volume of a mixture. The term concentration can be applied to any kind of chemical mixture, but most frequently it refers to solutes in homogeneous solutions. Meanwhile, spectrogram is a time-varying spectral representation (forming an image of graph) that shows how the spectral density of a signal varies with time. It is an instrument used to measure properties of light over a specific portion of the electromagnetic spectrum, typically used in spectroscopic analysis to identify materials. The purpose of this project was to develop the systems that can identify the concentration of a compound by using spectrogram. Using MATLAB, the chemical concentration can calculated based on the compound of the solution. By using Acrylic acid as an example; which the simplest unsaturated carboxylic acid which has double bond and carboxyl group in C3 one molecule with the formula CH2=CHCOOH, we can determine the concentration percentages of the compound that form acrylic acid. Based on the graph that plotted by using MATLAB, the area under graph calculate. With the area, we can calculate the concentration directly based on the data from HPLC-high performance liquid chromatography.